PROFESSIONAL DEVELOPMENT OF BEGINNING TEACHER TRAINERS OF DEGREE COURSES - Laurizete Ferragut Passos; Nayana Cristina Gomes Teles; Marta de Oliveira Gonçalves; Adriana Teixeira Reis (Editora da Universidade de Santa Cruz do Sul, 2016)
The research assumes that the presence of a renewed faculty has been working in the Teaching Degree and Pedagogy courses, specific contexts of initial teacher training. These training teachers are starting a career in higher education and part of them carries significant experience as a teacher of basic education. Knowing what constitutes the professional development of this trainer, beginner in a segment, higher education, and experienced in another, basic education, and reflect on the perception of their performance and their role as trainers of future teachers constituted the research objectives. For this article we will analyze the interview data from a beginning teacher in the Bachelor's Degree. The text is provided by the studies by Marcelo Garcia (1999); Day (2001); Wedge (2005); Imbernon (2009, 2011); Vaillant and Marcelo (2012); among others. The results show that the teacher realizes the process of their professional development to be always in progress, non-linear, crossed by different factors, with a permanent feeling of incompleteness; recalls the importance of the work period in basic education schools for their professional development and performance as a teacher trainer.